(3QSGdI aj GdehGRfIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3eMeO GdCejf Hf YeQ Hf eMeO GdOfa GdCfUGQi s)
(3ChdgG (B:s
(3bGd SjOi eMi GdOjf GdMeO ddg GdcGTa dWGFa GdCSQGQ GdCQHGH Gdgee hGdCHUGQ HeG efM ef eYGQa GdCfhGQ hHYO aEf ddfGXQ ai gPG GdYde GdPi fMf HUOOg hfXQ ai GdMceI GdEdgjI s
(3BNQgG (B:s
(3hdG CMH Cf CRjO Ydi gPG cTakG aEf HYV GdCSQGQ dGjfWb HgG YQa MJi jgJOi EdjgG ef ZjQ JYdje hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3fSNI ecQQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs